Zelo prezgodnji porod - Hrašovec, Andreja (Medicinski razgledi, 2008)
The development of neonatology in the past years has led to the survival of extremely preterm neonates. Early and late consequences for the child represent a huge public health problem. Most preterm deliveries occur in the group of pregnant women without risk factors. Screening tests for preterm delivery risk should be used in all pregnant women. Obstetric history and short cervix are, for the time being, the best predictors of high risk for preterm delivery. Besides the use of the prediction model for determining the risk for preterm delivery, which was elaborated on the basis of Slovene data on 150,000 deliveries, the goal of the study entitled Prediction of preterm delivery and prevention of very preterm delivery, which is part of the Research Programme P3-0124, is to perform additional tests for improvement of prediction. Furthermore, we intend to find the risk factors which can be influenced. Because of long term consequences, preterm delivery presents a huge health problem. Screening tests must be used in all pregnant women. In women with high risk, all known methods for the prolongation of pregnancy mustbe implemented if that does not hurt the mother and/or the baby. In the future, genomics, proteomics and other tests will allow individual prediction.
Keywords: Labor, Premature; Novorojenček, zelo nizke porodne teže; Porod prezgodnji; Etiology; Dejavniki tveganja; Diagnosis; Risk Factors; Stres psihološki; Infant, Very Low Birth Weight; Napovedna vrednost testov; childbirth; porod; Stress, Psychological; Chorioamnionitis; prezgodnji porod; Predictive Value Of Tests; novorojenčki; Horioamnionitis